Prediction of the crystal structures of axitinib, a polymorphic pharmaceutical molecule. (6th January 2015) - Vasileiadis, Manolis; Pantelides, Constantinos C.; Adjiman, Claire S.
Abstract: Organic molecules can crystallize in multiple structures or polymorphs, yielding crystals with very different physical and mechanical properties. The prediction of the polymorphs that may appear in nature is a challenge with great potential benefits for the development of new products and processes. A multistage crystal structure prediction (CSP) methodology is applied to axitinib, a pharmaceutical molecule with significant polymorphism arising from molecular flexibility. The CSP study is focused on those polymorphs with one molecule in the asymmetric unit. The approach successfully identifies all four known polymorphs within this class, as well as a large number of other low-energy structures. The important role of conformational flexibility is highlighted. The performance of the approach is discussed in terms of both the quality of the results and various algorithmic and computational aspects, and some key priorities for further work in this area are identified. Graphical abstract: Highlights: First ab initio prediction of the polymorphs of axitinib, a challenging pharmaceutical molecule. Successful application of a systematic procedure to identify polymorphs with one molecule in asymmetric unit. Analysis of strengths and weaknesses of state of the art for crystal structure prediction. Identification of future research needs and priorities in this area.